Algorithm for the Management of Patients with Cystic Maxillary Sinusitis - Nasretdinova Makhzuna Takhsinovna; Khatamov Zhakhongir Abruevich; Khayitov Alisher Adhamovich; Dustboboev Dilshod Sadulaevich (Scholars Digest Publishing, 2023)
The problem of selecting an adequate treatment for chronic cystic maxillary sinusitis remains relevant. Currently, the development of ways to improve the effectiveness of treatment of maxillary sinus cysts is of particular importance. The aim of the study was to develop a consistent tactics of surgical treatment of patients with maxillary sinus cysts (MCS). The basis of the study was a survey of 173 patients with cystic lesions of the maxillary sinuses. All patients were treated surgically. The study was conducted in different groups. Patients of the first group were offered an improved version of the removal of the maxillary sinus through the lower nasal passage. The assessment of clinical effectiveness is based on indicators of the quality of life of patients. An improved method of surgical treatment through the lower nasal passage showed a higher clinical efficacy. The difference in quality of life between the groups was 12 and 9 points, which means that the patients of the first group had a higher quality of life after treatment with improved technology.
Keywords: Chronic sinusitis, maxillary sinus cysts, the quality of life, sinustomy.